Chiral aziridine ring opening: facile synthesis of (R)-modletine and (R)-phenoxybenzamine hydrochloride - Viswanadh, N.; Velayudham, R.; Jambu, S.; Sasikumar, M.; Muthukrishnan, Murugan (Tetrahedron Letters, 2015)
A simple and efficient synthesis of chiral drugs (R)-mexiletine 1, an anti-arrhythmic drug and (R)-phenoxybenzamine hydrochloride 2, an anti-hypertensive drug has been described via controlled reductive ring opening of chiral aziridine as a key step. The target compounds 1 and 2 were obtained in overall yields of 34% and 10.5%, respectively. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Aziridine; Mexiletine; Phenoxybenzamine

Alternate synthesis of appetite suppressant (R)-2-benzylmorpholine employing Sharpless asymmetric epoxidation strategy - Viswanadh, N.; Mujumdar, P.; Sasikumar, M.; Kunte, S. S.; Muthukrishnan, Murugan (Tetrahedron Letters, 2016)
An alternate synthesis of (R)-2-benzylmorpholine 1, an appetite suppressant agent has been accomplished starting from readily available trans-cinnamyl alcohol employing Sharpless asymmetric epoxidation strategy as a key step, with an overall yield of 24%. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: (R)-2-Benzylmorpholine; Appetite suppressant; Sharpless asymmetric epoxidation

Transition metal free regio-selective C–H hydroxylation of chromanones towards the synthesis of hydroxyl-chromanones using PhI(OAc)2 as the oxidant - Viswanadh, N. (Chemical Communications, 2018)
The chromanone scaffold is considered as a privileged structure in drug discovery. Herein, we report a highly efficient PhI(OAc)2 mediated regioselective, direct C–H hydroxylation of chromanones. This method offers easy access to substituted 6-hydroxy chromanones in moderate to good isolated yields, thus paving the way for their pharmaceutical studies.

Synthesis, biological evaluation and molecular modeling studies of novel chromone/Aza-Chromone fused alpha-aminophosphonates as src kinase inhibitors - Bapat, S.; Viswanadh, N.; Mujahid, M.; Shirazi, A. N.; Tiwari, R. K.; Parang, K.; Karthikeyan, M.; Muthukrishnan, M.; Vyas, Renu (Journal of Scientific & Industrial Research, 2019)
A series of novel chromone/aza-chromone fused alpha-aminophosphonate derivatives were synthesized in good yields using silica chloride as the catalyst. All the synthesized compounds were tested for their c-Src kinase inhibitory activity. Aza-chromone compound showed Src kinase inhibition with an IC50 value of 15.8 mu M. The compounds were subjected to molecular docking and dynamics simulations to study the atomic level interactions with an unphosphorylated proto-oncogenic tyrosine protein kinase Src (PDB code 1Y57) as well as phosphorylated tyrosine protein kinase Src (PDB code 2H8H). Docking and molecular dynamic results revealed phosphorylated Src tyrosine kinase protein better results than unphosphorylated tyrosine Src kinase protein. Chemoinformatics study revealed the compounds had lead like properties. Machine learning (SVR) models were built to study the structure activity correlations. A CC of 0.835 was obtained when the SVR model was applied to the 17 synthesized compounds. It is envisaged that the work will provide guidelines for future drug design efforts for Src kinase inhibitors.

Synthesis, biological evaluation and molecular modeling studies of novel chromone/Aza-chromone fused α-aminophosphonates as Src kinase inhibitors - Bapat, Sanket; Viswanadh, N.; Mujahid, M.; Shirazi, Amir Nasrolahi; Tiwari, Rakesh; Parang, Keykavous; Karthikeyan, Muthukumarasamy; Muthukrishnan, M.; Vyas, Renu (Journal of Scientific and Industrial Research, 2019)
A series of novel chromone/aza-chromone fused α-aminophosphonate derivatives were synthesized in good yields using silica chloride as the catalyst. All the synthesized compounds were tested for their c-Src kinase inhibitory activity. Aza-chromone compound showed Src kinase inhibition with an IC50 value of 15.8 µM. The compounds were subjected to molecular docking and dynamics simulations to study the atomic level interactions with an unphosphorylated proto-oncogenic tyrosine protein kinase Src (PDB code 1Y57) as well as phosphorylated tyrosine protein kinase Src (PDB code 2H8H). Docking and molecular dynamic results revealed phosphorylated Src tyrosine kinase protein better results than unphosphorylated tyrosine Src kinase protein. Chemoinformatics study revealed the compounds had lead like properties. Machine learning (SVR) models were built to study the structure activity correlations. A CC of 0.835 was obtained when the SVR model was applied to the 17 synthesized compounds. It is envisaged that the work will provide guidelines for future drug design efforts for Src kinase inhibitors.